Role of Antioxidants in Helicobacter pylori Infection among patients with Cirrhosis: A Cross-Sectional Observational Study - Muhammad Yaseen, Muhammad Faisal Rashid, Farooq Ahmad Malik, Sanjay Kumar, Zahra Masood, Muhammad Usama (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Cirrhosis is frequently associated with impaired immune function and elevated oxidative stress, which may predispose to persistent Helicobacter pylori (H. pylori) infection. Objective: To evaluate the relationship between serum antioxidant levels and H. pylori infection in patients with liver cirrhosis and to determine whether antioxidant deficiencies are associated with infection prevalence and liver disease severity. Methods: This was a cross-sectional observational study conducted at Sahiwal Teaching Hospital, Sahiwal from November 2022 to May 2023. A total of 235 patients were enrolled in the study. Non-probability consecutive sampling was employed to recruit eligible participants. A structured proforma was used to record demographic data, etiology and severity of cirrhosis (Child-Pugh and MELD scores), clinical history, medication use, and lifestyle factors. Results: H. pylori infection was found in 124 (52.8%) patients. Antioxidant levels were significantly lower in infected individuals compared to non-infected counterparts (p < 0.001 for all markers). Strong inverse correlations were observed between antioxidant levels and liver disease severity (e.g., TAC vs. MELD: r = –0.41, p < 0.001). On multivariate analysis, low Vitamin C (OR = 2.45), low TAC (OR = 2.89), and Child-Pugh Class C (OR = 2.11) were independently associated with H. pylori positivity. Conclusion: Antioxidant deficiencies are significantly associated with H. pylori infection in cirrhotic patients and correlate with the severity of liver dysfunction. Keywords: H. pylori, Cirrhosis, Antioxidants, Oxidative stress, Child-Pugh score, Total Antioxidant Capacity.